A Diagnosis of English Language Teaching in Public Elementary Schools in Pasto, Colombia - Jesús Alirio Bastidas; Gaby Muñoz Ibarra (Asociación Colombiana de Profesores de Ingles, 2011)
English teaching in Colombian primary schools became a requirement because of the promulgation of the Law of Education in 1994. Taking into account that this decision produced some difficulties in the schools, a study was conducted to diagnose the state of English language teaching in primary schools in Pasto, Colombia. Data were gathered through classroom observation, a questionnaire, and interviews. The results showed that teachers are not well versed either in methodology or in the command of the English language; there was no English syllabus; didactic materials were nonexistent; and the children's lack of motivation was the most critical problem. Teachers, institutions and the government have to take into account these findings in order to improve English learning in primary schools.